2019
DOI: 10.2807/1560-7917.es.2019.24.29.1800446
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal vaccination coverages by age, sex and specific underlying risk conditions among middle-aged and older adults in Catalonia, Spain, 2017

Abstract: Background Recent published data on pneumococcal vaccination coverages among adults are scarce. Aim To update on pneumococcal vaccination uptakes among middle-aged and older adults in Catalonia. Methods We conducted a population-based retrospective observational study including 2,057,656 individuals ≥ 50 years old assigned to primary care centres managed by the Catalonian Health Institute on 1 January 2017 (date of data collection). An instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
0
31
0
2
Order By: Relevance
“…In accordance with other studies, we observed that people over the age of 65 are better vaccinated against influenza and pneumococcal disease. 16 , 18 , 29 31 Similarly, an Irish study found coverage rates of 28% against influenza and 16% against pneumococcus in adults at risk below 65 years of age and 60% against influenza and 36% against pneumococcus in adults above the age of 65. 18 It has been suggested that most countries are more devoted to vaccinating older rather than younger risk groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with other studies, we observed that people over the age of 65 are better vaccinated against influenza and pneumococcal disease. 16 , 18 , 29 31 Similarly, an Irish study found coverage rates of 28% against influenza and 16% against pneumococcus in adults at risk below 65 years of age and 60% against influenza and 36% against pneumococcus in adults above the age of 65. 18 It has been suggested that most countries are more devoted to vaccinating older rather than younger risk groups.…”
Section: Discussionmentioning
confidence: 99%
“… 15 For pneumococcal vaccination, other studies also reported low coverage rates ranging from 7% in Italy to 50% in immunocompromised patients in the United states and 60% in high-risk groups in Catalonia (Spain). 17 19 , 29 A possible reason for low coverage rates is that patients at risk are closely monitored by a specialist and therefore less often consult a general practitioner, which is the preferred vaccinator in Belgium. Specialists often do not approach patients about vaccination as this is considered the general practitioner’s task.…”
Section: Discussionmentioning
confidence: 99%
“…In a large cohort of 58,589 individuals in Australia, the vaccination coverage for the elderly people was 69% for the age group of 60–65 years for conjugate pneumococcal vaccine and the vaccination was more likely among those with comorbidities [ 18 ]. The results from another local study in Catalonia, Spain, showed that 38.7% had received PPSV-23 at any time during the last 5 years and only 0.7% at all age groups from the population study had received conjugate pneumococcal vaccine (PCV-13) in the previous 5 years [ 19 ]. Another study from one region of Greece with 318 participants (56.6%) had received a flu vaccine in 2018, while 50.8% received it annually in previous years' significant difference with the present study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…e results from another local study in Catalonia, Spain, showed that 38.7% had received PPSV-23 at any time during the last 5 years and only 0.7% at all age groups from the population study had received conjugate pneumococcal vaccine (PCV-13) in the previous 5 years [19]. Another study from one region of Greece with 318 participants (56.6%) had received a flu vaccine in 2018, while 50.8% received it annually in previous years' significant difference with the present study [20].…”
Section: Pneumococcal Vaccinementioning
confidence: 99%
“…After recommending sequential use of both vaccines for several years, now only PPV23 is generally recommended and the addition of PCV should be considered for the individual patient in a shared decision process (158). These uncertainties might contribute to the still low vaccination coverage in many countries (159)(160)(161)(162). Development of conjugate vaccines comprising more serotypes is ongoing and it might be worthwhile to consider the option of including different serotypes in pediatric compared to adult vaccines in order to reflect the distinct pattern of serotype prevalence in the different age groups.…”
Section: Conjugation Of Polysaccharide Antigensmentioning
confidence: 99%